Life against death : the psychoanalytical meaning of history - Brown, Norman Oliver, 1913-2002. (Middletown, Conn. : Wesleyan University Press ; Scranton, Pa. : Distributed by Harper & Row, 1985)
Product Description: A shocking and extreme interpretation of the father of psychoanalysis.
Introduction to the second edition / Christopher Lasch -- Acknowledgments -- Preface -- Part 1: Problem -- 1: Disease called man -- 2: Neurosis and history -- Part 2: Eros -- 3: Sexuality and childhood -- 4: Self and the other: narcissus -- 5: Art and Eros -- 6: Language and Eros -- Part 3: Death -- 7: Instinctual dualism and instinctual dialectics -- 8: Death, time, and eternity -- 9: Death and childhood -- Part 4: Sublimation -- 10: Ambiguities of sublimation -- 11: Couch and culture -- 12: Apollo and Dionysus -- Part 5: Studies In Anality -- 13: Excremental vision -- 14: Protestant era -- 15: Filthy lucre -- Rationality and irrationality -- Sacred and secular -- Utility and uselessness -- Owe and ought -- Time is money -- Giving and taking -- City sublime -- Immortality -- Human body -- Excrement -- Part 6: Way Out -- 16: Resurrection of the body -- Reference notes -- Bibliography -- Index.
Includes bibliographical references (pages 351-360) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Civilization -- Philosophy; Civilization -- Psychological aspects; Psychohistory; Psychoanalysis; Death instinct; Civilisation -- Philosophie; Civilisation -- Aspect psychologique; Psychohistoire; Psychanalyse; Pulsion de mort; psychohistory; psychoanalysis; PSYCHOLOGY -- Movements -- Psychoanalysis; Civilization -- Philosophy; Civilization -- Psychological aspects; Death instinct; Psychoanalysis; Psychohistory; Cultuurfilosofie; Seksualiteit